If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(3x + -11) = 7 + 7x Reorder the terms: 11x + -1(-11 + 3x) = 7 + 7x 11x + (-11 * -1 + 3x * -1) = 7 + 7x 11x + (11 + -3x) = 7 + 7x Reorder the terms: 11 + 11x + -3x = 7 + 7x Combine like terms: 11x + -3x = 8x 11 + 8x = 7 + 7x Solving 11 + 8x = 7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 11 + 8x + -7x = 7 + 7x + -7x Combine like terms: 8x + -7x = 1x 11 + 1x = 7 + 7x + -7x Combine like terms: 7x + -7x = 0 11 + 1x = 7 + 0 11 + 1x = 7 Add '-11' to each side of the equation. 11 + -11 + 1x = 7 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 7 + -11 1x = 7 + -11 Combine like terms: 7 + -11 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 2x+5=2-(x-9) | | c-7=21.95 | | 6+0.2r=-6 | | 3z^2+12z+13=0 | | 2k+6k=8 | | y-6-7(y-5)+5(6y+1)=y-6-7xy-5-5+5(6y+1) | | 7.5x=270 | | 3*42-(7+3)/2+5= | | 2(3ax-2y)-6ax=-3(ax+2y) | | 40=10-2y | | 7m=3m+4 | | 4(1+4n)= | | -4n+2+2n=-3(2n+2) | | 12(6y-4)= | | 0.8t-5=7 | | y=c+u-x | | 4x^2+17x=-18 | | y^2-8y=-13 | | 60c^2-38c-126=0 | | 60=h-3 | | 8r-7(r-8)+3(s-8)= | | 38a+15-36q=21 | | .375x+2.5=.75 | | 0.5r-0.25=0.5-0.25r | | 4.1z+5.8=5.3z+4.6 | | x^2+2*x-35=0 | | 5-(8+3x)=2x+3 | | 7(9+11y)= | | 2y=4x+7 | | 6x+3(45)=303 | | 3X[42-(7+3)*2]+5= | | 16s+23s-5=14s |